How Does Learning Affect Inflation After a Shift in the Exchange Rate Regime? - Papi, Laura (Washington, D.C. : International Monetary Fund, 1994)
This paper analyzes the consequences of a shift from a floating to a pegged exchange rate regime on the actual and expected inflation rate, in an environment of asymmetric information. Policymaking is endogenous and the public learns rationally. There are two main findings. First, there is a 'honeymoon effect' after the regime change, where inflation is lower than in the long run. Second, the asymmetric information outcome converges to that of symmetric information in the long run.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet